Fluorometric quantification of green fluorescent protein in tobacco leaf extracts - Robic, G.; Lacorte, C.; Miranda, E.A.
The main use of green fluorescent protein (GFP)is as a reporter system, where the existence of the protein is usually determined visually using fluorescent microscopy. Although fluorescence-based quantification of GFP is possible, background fluorescence in plants and in plant extracts was observed by our group. Another phenomenon we observed that makes quantification difficult is the increased level of GFP fluorescence in Nicotiana benthamiana leaf extracts, probably the result of dimerization of GFP molecules promoted by interaction with some component(s)of tobacco extracts. In the current work, the background fluorescence was minimized and the enhancement of GFP fluorescence in tobacco extracts was eliminated with the addition of urea to the measured solution so that a simple quantification assay for the GFP in the tobacco extracts could be established.
Keywords: GFP; QUANTIFICATION; FLUORESCENCE; TOBACCO